Electrochemical Evaluation of Titanium (IV) Oxide/Polyacrylonitrile Electrospun Discharged Battery Coals as Supercapacitor Electrodes. Issue 1 (2nd September 2020) - Aslan, Sema; Bal Altuntaş, Derya; Koçak, Çağdaş; Kara Subaşat, Hülya
Abstract: The TiO2 nanoparticles are electrospun with polyacrylonitrile (PAN) polymer solution onto the discharged battery coal (DBC) electrode and the results are evaluated as a supercapacitor. The morphology and chemical composition of the synthesized TiO2 nanoparticles and PAN+TiO2 nanocomposite fibers were characterized by Scanning electron microscopy, thermogravimetry and FTIR analysis. Supercapacitor measurements and electrochemical characterizations of the electrodes examined by cyclic voltammetry and electrochemical impedance spectroscopy. Electrochemical measurements showed that the best current value was obtained from PAN and TiO2 coated DBC. The performances of both PAN and PAN+TiO2 coated DBC electrodes were investigated as supercapacitors. PAN+TiO2 /DBC showed the best specific capacitance value of 156.00 F g −1 and PAN/DBC showed 74.93 F g −1 . In addition, PAN+TiO2 /DBC exhibited reliable stability performance over 2000.00 cycles. Abstract :